Modified approach for transcatheter correction of superior sinus venosus atrial septal defect: a case series. Issue 1 (17th January 2023) - Schleiger, Anastasia; Nordmeyer, Johannes; Kramer, Peter; Berger, Felix
Abstract: Background: Transcatheter correction of superior sinus venosus atrial septal defect (SVASD) with partial anomalous pulmonary venous drainage (PAPVD) of the right upper and/or right middle pulmonary vein (RUPV/RMPV) has recently been described as an alternative to surgical approach in a substantial number of patients. We describe a modified technical approach for transcatheter correction of SVASD using transoesophageal echocardiography (TOE) to confirm adequate stent landing zone and apposition and evaluate its feasibility, safety, and procedural success. Case summary: From 2019 to 2021, three consecutive patients received a transcatheter correction of SVASD with PAPVD by redirecting the superior vena cava and RUPV/RMPV to the left atrium by implantation of a custom-made covered Cheatham platinum stent (10-zig, length: 60–80 mm). Prior to stent implantation, a balloon testing was performed in the anticipated landing zone using TOE to confirm complete defect closure and unobstructed pulmonary venous drainage. Stent deployment and flaring of the interior stent portion were performed with TOE guidance to confirm adequate landing zone and apposition and to avoid residual shunt or pulmonary vein obstruction. Conclusion: Transcatheter correction of SVASD with PAPVD was performed without any complications. The follow-up period was 7.8, 13.6, and 29.8 months, respectively. During follow-up, no mortality, stent embolization, or obstruction of pulmonary venous drainage occurred. The TOE-guided modified transcatheter approach for correction of SVASD with PAPVD is safe and feasible with excellent post-procedural results and represents an alternative to surgical treatment in a pre-selected patient cohort.